AN ANALYSIS ON FINANCING BY SHARIA SAVING AND LOANS COORPORATIVE BAITUL TANWIL MUHAMMADIYAH RASAU JAYA TOWARD THE PROFIT OF MICRO, SMALL, AND MEDIUM-SCALE BUSINESS PEOPLE IN SUB-DISTRICT OF RASAU JAYAâ€ - B01109099, M RULLY SOFIYANTO SOFIYANTO (Jurnal Pembangunan dan Pemerataan, 2015)
The problems of this research were â€œHow much was the profit made by Micro, small, and medium-scale business people before and after receiving financing from the Sharia Savings and Loans Cooperative Baitul Tamwil Muhammadiyah Rasau Jaya, and whatobstacles were faced by these business people in running their business, and what did they do to overcome these obstacles?From the research, it was revealed that financing by Sharia Savings and Loans Cooperative Baitul Tamwil Muhammadiyah Rasau Jaya played a role in increasing the Profit of micro, small, and medium-scale business people, where a low profit level before receiving the funding which was 70% of the respondents, to date the figure had gone down to 20% after they received the financing. This indicated a positive condition where there were fewer respondents who had low profit. It occurred due to a wide range of obstacles faced and the way they dealt with the problems.The results of the research showed that financing provided by Sharia Savings and Loans Cooperative Baitul Tamwil Muhammadiyah Rasau Jaya was very helpful in increasing the profit of micro, small, and medium-scale business people as well as improving productivity which subsequently led to the welfare of the cooperativeâ€™s members who need capital for their business.Keywords: Financing, Profit.